Shakespeare arean hypertexts in communist Bulgaria - Alexander Shurbanov (Ilha do Desterro)
Since the first days of the reception of Shakespeare’s work in Bulgaria during the second half of the nineteenth century down to the present time two of his tragedies, Romeo and Juliet and Hamlet, have held an unrivalled sway on the national stage and over the people’s minds. Another one, Othello, was produced very frequently in the beginning, though often by non-Bulgarian troupes, and yet another, Macbeth, was a set text at the schools for many decades but rarely took the fancy of theatre directors and audiences.